A retrospective clinical study and management of ingested Indian currency coin found in the oesophagus among paediatric age group - M. S., Sudhakar Rao; Karade, Deepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Foreign body ingestion is a common event in children and carries significant morbidity and mortality. Indian currency coins are found to be the common ingested foreign bodies hence, to be treated accordingly. Methods: A 7 years retrospective review of 133 children diagnosed, admitted and managed for “ingested Indian currency coin” between January 2011 to December 2017 in the Department of Oto-rhino-laryngology and Head and Neck surgery, Vijayanagar Institute of Medical Sciences, Ballari, Karnataka, India. A plain radiograph of the relevant views of neck and chest were taken to identify the foreign body. Results: There were 80 (60.2%) males and 53 (39.8%) females, ranging in age from 6 months to 15 years. Most of the patients 98 (73.7%) presented within 12 hours of the coin ingestion. 109 patients presented with one or more symptoms, common being vomiting 83 (62.4%). Coin was located mostly at the cricopharynx 111 (83.5%). Coin removal was possible using Macintosh laryngoscope and Magill’s forceps in 106 (79.7%) patients, and 27 (20.3%) patient’s required rigid oesophagoscope. Conclusions: Indian currency coin ingestion is commonly found in cricopharyngeal area of the oesophagus among preschool age group. The duration of retention of the foreign body, procedural time, hospital stay of the patient, diameter of the coin in both the genders have no impact on clinical outcome on retrieval of them.